The andragogical value of content knowledge method: the case of an adult education programme in Kwa-Zulu Natal Province of South Africa. Issue 9 (September 2021) - Akintolu, Morakinyo; Letseka, Moeketsi
Abstract: The South African government has made a significant progress in the area of policy development and practice for Adult Education since independence in 1994. Still, there has been a tremendous increase in the number of adults without education. For example, KwaZulu-Natal, one of the provinces in South Africa, still recorded an increased number of illiteracy rate among adults, which further causes poverty and unemployment. The focus of this study is to explore the extend concept and ideas of andragogy are used by adult facilitators in delivering the content knowledge and how is andragogy effectively used in the knowledge transfer in Adult Education Programme in KwaZulu-Natal province. The study explores the concept of andragogy through the theoretical lens of the Theory of Andragogy. The qualitative research method was used for the study. The thematic data analysis revealed that the stakeholder involved in the planning and policymaking could do more to improve the curriculum by making it adult-friendly and adjusting the teaching method by considering the experience of adult learners during the teaching and learning process. This will make in support of the theory of andragogy which believe in the art and science of teaching an adult. It was also of importance that the study shows the level of involvement of adult learners in determining the learning method. Abstract : Andragogy, Adult education, Adult facilitators, Adult learners, Content knowledge